Towards a Taxonomy for Classifying Intuitive Usability Prediction Strategies in Non-Experts. (September 2016) - Sublette, M.A.; Carswell, C.M.; Lee, M.; Kent, T.
In order to compare the strategies consumers use to make predictions about the ease-of-use of products, the authors conducted a card sorting exercise with subject-matter experts (SMEs) to refine a coding scheme from current, widely-used usability definitions and measurement tools. Nine SMEs sorted 83 cards containing aspects found in usability definitions, guidelines, measurement tools and descriptions. The resulting fifteen clusters define a coding scheme that is both comprehensive and flexible. The refined taxonomy does not seek to redefine usability, but to provide a mechanism for researchers wanting to use a coding scheme that includes methods for classifying strategies such as usability attribution to system features, metacognitive behaviors (planning and evaluating), and exemplar-based strategies (memory for performing similar tasks).